Anatomically-preserved cordaitalean trees from Lower Pennsylvanian (Langsettian) dryland alluvial-plain deposits at Joggins, Nova Scotia - Falcon-Lang, Howard (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT Recent discoveries at Joggins, Nova Scotia have altered our understanding of the Pennsylvanian tropical biome. Of particular signiﬁcance has been the recognition of seasonal dryland ecosystems, compositionally distinct from the peat-forming wetland rainforests. Here I describe two anatomically-preserved fossil plant specimens from dryland alluvial plain facies. The ﬁrst specimen, Mesoxylon cf. sutclifﬁ i, is previously unknown from Joggins. It is a septate cordaitalean axis with mesarch leaf traces and a non-sympodial vasculature. Where found as isolated blocks, the secondary xylem of this plant has previously been classiﬁed as Dadoxylon recentium. The axis exhibits subtle growth interruptions suggestive of tropical rainfall seasonality, while associated traumatic zones may record ﬁre-damage. The second specimen is a Dadoxylon stump rooted within well-drained ﬂoodbasin soils. It conﬁrms earlier conjecture, based on parautochthonous assemblages, that cordaitalean trees grew in inter-channel areas. Together these new specimens improve our knowledge of the composition and ecology of seasonal dryland vegetation at Joggins.